Speech Therapists’ Readiness to Perform the Functions of Speech and Language Therapists in Healthcare Institutions: A Transitional Period - Leniv, Zoriana (Educological discourse, 2026)
The article examines the urgent issue of training speech-language pathologists and speech and language therapists (SLTs) for the modern healthcare system of Ukraine, which is undergoing active transformational processes related to both sectoral reform and wartime challenges. In the context of a significant increase in the number of patients with neurogenic disorders of speech, swallowing, and communication, the professional preparation of specialists capable of working effectively within multidisciplinary teams becomes particularly important. The focus of the article is the development and pilot testing of a professional development programme for speech-language pathologists and acting speech and language therapists employed in healthcare institutions during the transitional period preceding the official implementation of the SLT profession in accordance with the Law of Ukraine «On Rehabilitation in the Healthcare Sector». The aim of the study is to design an effective model of continuing professional education for clinical speech-language pathologists and SLTs that meets the needs of practical work, complies with current legislation, and aligns with international standards. The methodological basis of the research includes a set of theoretical and empirical methods: an analysis and synthesis of scholarly sources, a comparative-analytical approach, a content analysis of regulatory documents, as well as a survey of 64 specialists (speech-language pathologists, SLTs, and acting SLTs) to identify key problems in their professional activity. The results show that the majority of respondents (over 56%) experience a lack of knowledge and practical skills; more than 70% report the absence or incompleteness of SLT-related documentation and highlight insufficient material and organisational support. Despite these challenges, respondents demonstrate a high level of interest in professional development: 50% prefer short online courses, while 41.9% opt for long-term blended learning programmes. Based on the collected data, a three-module SLT professional development program was improved: Organizational and legal module – legal foundations of practice, teamwork, professional ethics, and documentation; Medical and rehabilitation module – essential knowledge in neurology, aphasiology, phoniatrics, diagnostic methods, and management of complex clinical cases; Psychological and pedagogical module – innovative speech-rehabilitation techniques and alternative communication strategies. The program, developed on the basis of practical experience, fully complies with the Professional Standard «Speech and Language Therapist» and was piloted at the Lviv Medical Academy named after Andrey Krupynskyi in cooperation with the International Institute of Inclusion through a blended format of in-person and online training. During the pilot phase, the program proved effective in enhancing the competencies of the targeted specialists. The conclusions emphasise that successful implementation of the SLT profession in Ukraine requires the standardisation of documentation, methodological resources, and materials; the creation of a national system of continuous professional development; and the provision of fair remuneration for SLTs. The proposed programme aims to address the existing workforce and educational gaps, improve the quality of rehabilitation services, adapt classical clinical speech-language pathology practice to medical standards, and contribute to shaping a modern model of rehabilitation for individuals with speech and language disorders within Ukraine’s healthcare system.